DIVERSITY OF TREE SPECIES IN PROHIBITION FOREST IMBO PUTUI OF PETAPAHAN VILLAGE KAMPAR REGENCY IN RIAU PROVINCE - Widia Safitri; Defri Yoza; Yossi Oktorini (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2019)
Imbo Putui Prohibition Forest was located in Petapahan Village, Tapung District, Kampar Regency, Riau Province. The area of Imbo Putui Prohibition Forest is 250 ha. Imbo Putui Prohibition Forest was known to store a great variety of species, both flora and fauna. There are 59 different types of trees from 24 different families and there are 6 types of trees that have an important value index (INP) of more than 15%, the type was medang, mempening, kelat, meranti, lalan and kempas. It was necessary to do research with the title of Tree Species Diversity in Imbo Putui Prohibition Forest in Petapahan Village, Kampar Regency, Riau Province, which aims to determine the diversity of tree species found in the Imbo Putui Indigenous Forest. So that the value of plant species diversity in the Imbo Putui Prohibition Forest was obtained was high, which was 3.28. The value of Imbo Putui Indigenous Forest Prohibition species was high, which was 8.68. The evenness index value in the Imbo Putui Prohibition Forest was high at 0.80.